Mining 3D genome structure populations identifies major factors governing the stability of regulatory communities - Chao Dai (Nature Portfolio, 2016)
3D genome structures are plastic and vary from cell to cell even in an isogenic sample. Here, the authors present an approach to identify frequent 3D chromatin clusters across a population of genome structures, either deconvoluted from ensemble-averaged Hi-C data or from a collection of single-cell Hi-C data.